Penerapan Media Film Animasi dalam Meningkatkan Kemampuan Agama Anak Usia 5-6 Tahun di RA Al-Barkah Medan Helvetia - Harahap, Salamiyah Nur Hakim; Khadijah, Khadijah; Daulay, Sholihatul Hamidah (Darul Yasin Al Sys, 2024)
This research was conducted at RA.Al-Barkah Medan Helvetia, Medan City, where initially during the pre-cycle phase, researchers observed a lack of religious knowledge among 5-6 year-old children at RA. Al-Barkah. This was attributed to the limited use of media in learning. Therefore, the researchers initiated a study titled